Dye-sensitized solar cells based on hierarchically structured porous TiO2 filled with nanoparticles1. Issue 21 (7th June 2015) - Zhao, Zhenxuan; Liu, Guicheng; Li, Bo; Guo, Lixue; Fei, Chengbin; Wang, Yajie; Lv, Lili; Liu, Xiaoguang; Tian, Jianjun; Cao, Guozhong
<x xml:space="preserve">Abstract</x> DSCs based on hierarchically structured porous TiO2 filled with nanoparticles exhibited the highest PCE of 9.7%.